EVALUASI KEANDALAN BANGUNAN RUSUNAWA UNNES DITINJAU DARI PERSEPSI MAHASISWA YANG MENGHUNINYA - -, Diharto; Nugroho, Ristya Mulia (Semarang State University, 2012)
The nature of this evaluation on building of Rusunawa (student flats) Unnes based on a desire to know the extent to which perceptions of the occupants of the building Rusunawa about Reliability of Â Rusunawa. The reliability of this building include requirements for safety, health, comfort, and convenience. Safety aspects include: building structure, building capacity of Rusunawa against fire and building capabilities of Rusunawa the dangers of lightning and electrical hazards. Health aspects include: ventilation systems, lighting systems, water supply systems and sanitation, use of building materials. Comfort aspects include: the space in the building, the condition of the air in the room, the view, the level of vibration and noise. Aspects include the ease of convenience to the relationship, from, and within the building. The research objective was to determine the reliability of building Rusunawa UNNES based on student perceptions that inhabit Rusunawa. This study uses descriptive quantitative approach. In this study there are two variables: the independent variable and the dependent variable. The independent variable is the students' perceptions of residents, while the dependent variable is the reliability of the building. Data analysis using descriptive analysis percentage. Reliability buildings Rusunawa UNNES included in both categories with a percentage of 78.44%. With the results of research on every aspect of the building itself is Reliability: (a) the safety aspect = 75.56%, (b) health aspect = 80.87%; (c) Aspects of comfort = 76.82%; (d) Aspects ease = 77.71%.Latar belakang evaluasi pada bangunan Rusunawa Unnes didasari pada keinginan untuk mengetahui sejauh mana persepsi dari penghuni Rusunawa tentang Keandalan dari bangunan Rusunawa. Keandalan dari bangunan ini meliputi persyaratan keselamatan, kesehatan, kenyamanan, dan kemudahan. Aspek keselamatan meliputi: struktur bangunan gedung, kemampuan bangunan Rusunawa terhadap bahaya kebakaran dan kemampuan bangunan Rusunawa terhadap bahaya petir dan bahaya kelistrikan. Aspek kesehatan meliputi: sistem penghawaan, sistem pencahayaan, sistem air bersih dan sanitasi, penggunaan bahan bangunan. Aspek kenyamanan meliputi: ruang gerak dalam bangunan gedung, kondisi udara dalam ruang, pandangan, tingkat getaran dan kebisingan. Aspek kemudahan meliputi kemudahan hubungan ke, dari, dan di dalam bangunan. Tujuan penelitian adalah untuk mengetahui keandalan bangunan Rusunawa UNNES berdasarkan persepsi mahasiswa yang menghuni Rusunawa. Penelitian ini menggunakan pendekatan deskriptif kuantitatif. Dalam penelitian ini terdapat dua variabel yaitu variabel bebas dan variabel terikat. Variabel bebas adalah persepsi mahasiswa penghuni, sedangkan variabel terikat adalah keandalan bangunan. Analisis data penelitian menggunakan analisis deskriptif persentasi. Keandalan bangunan Rusunawa UNNES termasuk dalam kategori baik dengan persentasi sebesar 78,44%. Dengan hasil penelitian terhadap setiap aspek Keandalan bangunan sendiri adalah: (a) Aspek keselamatan = 75,56%; (b) Aspek kesehatan = Â 80,87%; (c) Aspek kenyamanan = 76,82%; (d) Aspek kemudahan = 77,71%.